2023
DOI: 10.3389/feart.2022.1068536
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of rupture directivity effects on strong ground motion during the 8 January 2022 MS6.9 Menyuan earthquake in Qinghai, China

Abstract: On 8 January 2022, an MS6.9 earthquake occurred in the Menyuan county, Qinghai province at the northeastern margin of the Tibetan Plateau. A dense observatory network consisting of accelerographs and intensity meters has obtained many acceleration recordings in this region, which previously had only a few strong motion recordings. Using acceleration data recorded by 141 accelerographs and micro-electro mechanical system (MEMS)-based intensity meters within 100 km of the causative fault, we investigated the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, the impact of intense pulse-like ground motions on the seismic response of mid-rise modular structures has been investigated by (Emamikoupaei et al ., 2023) and found that there is a loss of stiffness and strength of mid-rise buildings under forward-directivity pulse-like ground motions. Additionally, the spatial distribution and attenuation characteristics of the near-source ground motion during the Mw 6.9 Menyuan earthquake in Qinghai, China have been examined by (Xie et al ., 2023). Further, significant damage to non-engineered RC buildings in the 2011 Sikkim earthquake for near-source ground motions has been reported by (Wani et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the impact of intense pulse-like ground motions on the seismic response of mid-rise modular structures has been investigated by (Emamikoupaei et al ., 2023) and found that there is a loss of stiffness and strength of mid-rise buildings under forward-directivity pulse-like ground motions. Additionally, the spatial distribution and attenuation characteristics of the near-source ground motion during the Mw 6.9 Menyuan earthquake in Qinghai, China have been examined by (Xie et al ., 2023). Further, significant damage to non-engineered RC buildings in the 2011 Sikkim earthquake for near-source ground motions has been reported by (Wani et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%